If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9x) + (5x) + (9 + x) = 0 Remove parenthesis around (9 + x) (9x) + (5x) + 9 + x = 0 Reorder the terms: 9 + (9x) + (5x) + x = 0 Combine like terms: (9x) + (5x) = 14x 9 + 14x + x = 0 Combine like terms: 14x + x = 15x 9 + 15x = 0 Solving 9 + 15x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 15x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 15x = 0 + -9 15x = 0 + -9 Combine like terms: 0 + -9 = -9 15x = -9 Divide each side by '15'. x = -0.6 Simplifying x = -0.6
| (x+15)+(4x-20)= | | 40k+100=30k+1q | | 4.4q-1.3-5.6q=0.2q-1.3 | | X=95+.05X | | 4(x-1)+3(x-2)=4 | | 7m-32=47 | | 7(w-3)=-2w-48 | | 3T+3+5T-7T=3+2 | | 10(c-1)=2(2c-5) | | 97.55-1.71/1.71x100= | | 60t^2+120t+60=0 | | -6(2t+2)=-72 | | x=138.5+-0.75y | | 10(s-8)=-163 | | 360x+270y=49860 | | 25m+15n= | | X^2+5(3x-1(2))= | | 174/x=58 | | 7(4s+2)=126 | | X+X-7=93 | | 8(2l+8)=160 | | y-0=-2(x-1) | | 6w=12-2w+4 | | -2(x-5)+14=22 | | 3w+5=2w-7 | | (Q-3)*5=10 | | 3X+500=50 | | 5(x+2)+3(x-7)=61 | | 3x-2x=303 | | y^2-2y-2xy+2x=0 | | 10x+15x=40 | | -2x-13=9 |